DIRECTIONS TO REDUCE THE LEVEL OF RISK IN THE AUDIT OF ASSETS - ugli, Ovlayev Sukhrob Temur (Research Parks Publishers, 2023)
The use of international standards in auditing activities leads to an increase in the quality of audit inspections. In order to improve the quality of audits, it is necessary to pay attention to the use of reducing the level of risk in the audit of assets. In this article, proposals for reducing the level of risk in the audit of assets have been developed.